Peningkatan Hasil Belajar Siswa Pada Penyelesaian Soal Cerita Perbandingan Menggunakan Model Think,Pair and Share - Islamy, Diah Putri; Ivana, Ivana; Desliyanah, Sherly (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2025)
Learning outcomes are one form of student ability that can be observed in research. Student learning outcomes in solving mathematical story problems on comparison material are still relatively low, this is because students' abilities still do not understand the change of story problems into complete mathematical sentences and the ability to use logical thinking in comparison is also still low. So in this study, the Think, Pair and Share (TPS) learning model was carried out on 20 sixth grade students at Paramount Elementary School, Palembang. Based on the results of the study, there was an increase in learning outcomes with an average student score of 79.8, 8% higher than the previous average score. With this TPS learning model, it also increased student activeness in discussions and student confidence in presenting in front of the class to deliver group discussion results, namely 55.3%.The TPS learning model that is applied can also train students' self-confidence and courage in expressing their opinions, in this case the ability to deliver group presentations is demonstrated by 8 students from 4 study groups who clearly convey their group's opinions.